2010
DOI: 10.1002/adfm.201000736
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Propagating Domino‐like Reactions in Oxidized Graphite

Abstract: Graphite oxide (GO) has received extensive interest as a precursor for the bulk production of graphene‐based materials. Here, the highly energetic nature of GO, noted from the self‐propagating thermal deoxygenating reaction observed in solid state, is explored. Although the resulting graphene product is quite stable against combustion even in a natural gas flame, its thermal stability is significantly reduced when contaminated with potassium salt by‐products left from GO synthesis. In particular, the contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
282
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 322 publications
(292 citation statements)
references
References 36 publications
6
282
0
4
Order By: Relevance
“…[4][5][6] Very recently, similar to some other members of the family of carbon-based materials, such as expanded graphite, graphite oxide and carbon nanotubes, graphene has attracted interests in scientific field as a flame retardant additive. 7,8 Kim et al 9 demonstrated that graphene is actually thermally stable even after exposing it to a flame, clearly indicating the high intrinsic flame resistance of graphene. In addition, there are some other reports regarding the application of graphene as a flame retardant additive in polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Very recently, similar to some other members of the family of carbon-based materials, such as expanded graphite, graphite oxide and carbon nanotubes, graphene has attracted interests in scientific field as a flame retardant additive. 7,8 Kim et al 9 demonstrated that graphene is actually thermally stable even after exposing it to a flame, clearly indicating the high intrinsic flame resistance of graphene. In addition, there are some other reports regarding the application of graphene as a flame retardant additive in polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…Weight loss at the rst stage is accelerated by the incorporation of GO nanosheets as can be seen in TGA and DTA results. Increased heat transfer due to the high thermal conductivity of GO or potassium salt impurities in GO 24) may be the cause of the promoted thermal degradation at lower temperature. However, the weight loss at the second stage is retarded to higher temperature by the GO nanosheets.…”
Section: Resultsmentioning
confidence: 99%
“…[ 22 ] The purifi ed GO, with typical lateral size of a few microns, was dried and redispersed in deionized water to create dispersions. SWCNTs were …”
Section: Methodsmentioning
confidence: 99%
“…Since GO can undergo partial deoxygenation upon gentle heating, [ 22 ] further work is also needed to evaluate the long term stability of devices with GO based modifying layers.…”
mentioning
confidence: 99%